A Comparative Study on the Effectiveness of Using Direct and Audiovisual Methods for Enhancing Students Listening Comprehension - Faidhatul Atiyah; Lidiyatul Izzah (English Language in Focus (ELIF), 2019)
The present study aims to compare experimentally direct and audio-visual method in terms of their effectiveness in students listening comprehension. Another purpose of the study is to help the teachers to find out the most effective way of teaching listening in the classroom. This study was conducted in MTS Al-Hamid, and 46 students of two classes were selected as the sample participants. In choosing the sample, the writer used a cluster random sampling technique. The subjects were assigned as experimental and control groups. This research used post-test only toward the experimental and control group. Data were gathered through the listening test in both the control and experimental group. While the experimental group learned English by implementing the audiovisual method, the control group was instructed by the audiovisual method. In the end, the results were statistically analyzed. Based on the result, the use of audio-visual method had a positive effect on the enhancement of students listening comprehension.